Bacteria that promote plant growth and the use of rock dust in the initial crop of non-conventional vegetables (Research, Society and Development, 2022)
The objective was to investigate the effect of inoculation of plant growth-promoting bacteria strains on the initial production of nasturtium (Tropaeolum majus L.), vine spinach (Basella rubra L.) and hibiscus (Hibiscus sabdariffa L.). For this, two experiments were implemented in the Experimental Sector of the José do Rosário Vellano University, in a randomized block design, in a 2 x 7 factorial scheme, with 3 replications. In the first experiment, two cultivars of T. majus (common and hybrid) and seven treatments in the soil (use of KCl, without potassium source, use of phonolite and phonolite associated with inoculation with four strains) were evaluated. In the second experiment, two unconventional vegetable species (T. majus and B. rubra) and 7 soil treatments were evaluated (use of KCl, without potassium source, use of phonolite and phonolite associated with inoculation with four strains of BPCV). The use of phonolite associated with inoculation with bacterial strains Ab-V5, UNIFENAS 100-13 and UNIFENAS 100-94 increased the production of fresh weight of shoots and roots of T. majus. The inoculation of plant growth-promoting bacteria strains associated with the use of phonolite had no significant influence on the initial growth of the species B. rubra and H. sabdariffa.